Flow cytometry assay for the detection of single-copy DNA in human lymphocytes. Issue 15 (16th June 2020) - Uno, Naoki; Kaku, Norihito; Morinaga, Yoshitomo; Hasegawa, Hiroo; Yanagihara, Katsunori
Abstract: Specific nucleic acid sequences can be detected in individual cells by in situ hybridization. However, when very few copies of a target sequence are present per cell, its signal is undetectable by flow cytometry. Although various approaches have been developed to increase fluorescence signals for in situ hybridization, flow cytometric detection of specific genomic DNA sequences has not been established. Here, we present a flow cytometry assay for detection of single-copy genomic sequences in human lymphocytes using in situ PCR with universal energy transfer-labelled primers.